2018
DOI: 10.1096/fj.201800078rr
|View full text |Cite
|
Sign up to set email alerts
|

SIRT7 functions in redox homeostasis and cytoskeletal organization during oocyte maturation

Abstract: SIRT7, a member of the sirtuin family, with coenzyme NAD catalyzes protein deacetylation and has been implicated in multiple biologic processes; however, its function in mammalian oocytes remains to be explored. Here, we report disrupted meiotic maturation upon specific knockdown of SIRT7 in mouse oocytes. In particular, disorganized spindle/chromosomes and the loss of the cortical actin cap are readily observed in SIRT7-depleted oocytes, generating aneuploid eggs. Furthermore, we found that SIRT7 depletion ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 52 publications
3
26
0
Order By: Relevance
“…In some inflammatory-related lung diseases, activated inflammatory cells like neutrophils and macrophages are thought to release considerable amounts of ROS, which in turn promote inflammation and trigger the development of other related diseases [29]. SIRT7 overexpression suppressed NO and ROS secretion in LPS-treated DCMECs, indicating that SIRT7 can suppress the initiation of inflammation by inhibiting NO and ROS production under normal conditions, which is consistent with a previous work [30]. A recent study demonstrated that SIRT7 is also involved in the regulation of mitochondrial homeostasis by deacetylating GABP β 1, which is important in regulating mitochondrial genes [31].…”
Section: Discussionsupporting
confidence: 90%
“…In some inflammatory-related lung diseases, activated inflammatory cells like neutrophils and macrophages are thought to release considerable amounts of ROS, which in turn promote inflammation and trigger the development of other related diseases [29]. SIRT7 overexpression suppressed NO and ROS secretion in LPS-treated DCMECs, indicating that SIRT7 can suppress the initiation of inflammation by inhibiting NO and ROS production under normal conditions, which is consistent with a previous work [30]. A recent study demonstrated that SIRT7 is also involved in the regulation of mitochondrial homeostasis by deacetylating GABP β 1, which is important in regulating mitochondrial genes [31].…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our results, sirtuins, including SIRT7, have been reported to be key activators of antioxidant and redox signaling. 38,39 To the best of our knowledge, this is the first study illustrating that exosomal miR-17-5P restores ovarian function, rescues CTX-damaged hGCs and alleviates OS by inhibiting the expression of SIRT7 and its downstream target genes (PARP1, γH2AX and XRCC6) ( Figure 7). γH2AX, XRCC6, and PARP1 are critical mediators of DNA repair.…”
Section: Discussionmentioning
confidence: 93%
“…The related primers are listed in Table . Plasmid construction and mRNA synthesis were conducted as we reported previously (Gao et al, ). In brief, PCR products were cloned into the pCS2 + vector with Myc tags, and cRNAs were made using in vitro transcription with SP6 mMESSAGE mMACHINE (Ambion) according to the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%